2021
DOI: 10.1038/s41565-021-00929-w
|View full text |Cite
|
Sign up to set email alerts
|

Role of bacterial motility in differential resistance mechanisms of silver nanoparticles and silver ions

Abstract: Unlike conventional antimicrobials, the study of bacterial resistance to silver nanoparticles (AgNPs) remains in its infancy and the mechanism(s) through which it evolves are limited and inconclusive. The central question remains whether bacterial resistance is driven by the AgNPs, released Ag(I) ions or a combination of these and other factors. Here, we show a specific resistance in an Escherichia coli K-12 MG1655 strain to subinhibitory concentrations of AgNPs, and not Ag(I) ions, as indicated by a statistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
90
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(108 citation statements)
references
References 65 publications
6
90
0
Order By: Relevance
“…It is a well-known fact that microbes develop resistance over a period of time upon continuous exposure to the antimicrobial substance . In the case of Gram-negative bacteria, the presence of the sil operon gene encoded with two efflux pumps and two periplasmic silver-binding chaperone proteins has been shown to act synergistically in driving out the silver ions. , Therefore, we performed the antibacterial resistance study using E. coli and S. aureus up to 10 passages, wherein ∼30% of the cells were killed in each cycle and thereby allowing the viable colonies for further growth to check any mutation acquired during the subsequent passages. The antibacterial resistance was monitored through the optical density measurements at the end of each passage, and the results are presented in Figure S7.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is a well-known fact that microbes develop resistance over a period of time upon continuous exposure to the antimicrobial substance . In the case of Gram-negative bacteria, the presence of the sil operon gene encoded with two efflux pumps and two periplasmic silver-binding chaperone proteins has been shown to act synergistically in driving out the silver ions. , Therefore, we performed the antibacterial resistance study using E. coli and S. aureus up to 10 passages, wherein ∼30% of the cells were killed in each cycle and thereby allowing the viable colonies for further growth to check any mutation acquired during the subsequent passages. The antibacterial resistance was monitored through the optical density measurements at the end of each passage, and the results are presented in Figure S7.…”
Section: Resultsmentioning
confidence: 99%
“…37−39 A recent study demonstrated that the propensity of microbial mutation is substantially less with ionic silver over silver nanoparticles and thereby highlighted the advantage of ionic silver. 40 Although several research works have been actively pursued to develop silver-based coatings to encounter the disinfection challenges, the majority of them are focused on silver nanoparticles or metallic silver coatings. 41−43 Silvercontaining photocatalysts have also been developed to achieve a high bactericidal performance, but their high-temperature synthesis and difficulties associated with additive-free coatings limit their application domains.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, AgNPs were effective in disrupting the morphology and structure and inhibiting biofilm formation of multidrug-resistant Pseudomonas aeruginosa [ 156 , 157 ]. In contrast, recent studies have shown the potential of AgNPs to stimulate AR in Escherichia coli K-12 MG1655 strain and the transfer of ARGs from E. coli K-12 LE392 to Pseudomonas putida KT2440 at environmentally relevant concentrations [ 158 , 159 ]. The results of these studies demonstrate that microorganisms are gradually becoming resistant to AgNPs as large quantities of the nanoparticles are produced annually and incorporated into consumer products worldwide.…”
Section: Drivers Of Antimicrobial Resistancementioning
confidence: 99%
“…Moreover, bacterial isolates lacking expression of fimbriae have demonstrated reduced growth, adhesion, biofilm formation and virulence, thereby resulting in low infections and improved survival in animal models and humans when infected with the virulent strains 8 . Hence, a need for better antimicrobial agents that can specifically target the cell wall and/or adherent fimbriae expression cannot be overstated, and engineered nanomaterials (ENMs) may have the potential to serve as the next generation antimicrobial agent 9 .…”
Section: Introductionmentioning
confidence: 99%